Time-dependent variation of POF Bragg grating reflectivity and wavelength submerged in different liquids. (1st September 2017) - Marques, C.A.F.; Pospori, A.; Webb, D.J.
Highlights: A study of time-dependent variation of mPOFBG array sensors is reported. Both the reflection and the wavelength shift were monitored over 90 days. mPOFBGs achieved long-term drifts in PMMA, due to the sensitivity of PMMA to water. TOPAS mPOFBGs revealed a much improved behavior for long-term liquid-monitoring systems. TOPAS is a good option for this type of applications and even in corrosive environments. Abstract: In this work, we investigate the time-dependent variation of both the reflectivity and resonance wavelength of microstructured polymer optical fiber Bragg grating (mPOFBG) array sensors embedded in silicone rubber and polyurethane resin diaphragms in contact with water and aircraft fuel, respectively. The array sensors were inscribed using two different phase masks with pitches of 557.5 and 580 nm and the thermal annealing of the inscribed fiber was used to change the Bragg wavelengths. Both the reflection and the resonance wavelength shift were monitored over 90 days submerged in liquid and two studies were investigated. In the first study, in addition to the mPOFBGs coated with the diaphragm, also the rest of the fiber is totally protected between the sensors with the same material used for diaphragms. On the other hand, in the second study, the fiber between sensors is unprotected – in direct contact with liquid. PMMA and TOPAS fibers were used and this study suggests that TOPAS fiber should be a good option for long-term liquid monitoring applications.